Rola organizacji pozarządowych w działalności gospodarczej na przykładzie fundacji - Raszewska-Skałecka, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
The role of non-governmental organizations in an enterprise seems to be an important issue due to the difference in the information on running an enterprise by the foundations and associations, which are provided in literature. In the case of non-governmental enterprise organizations there seems to be a problem in the differentiation between an enterprise and charter enterprise. The charter not always states the type of enterprise an organization may be running. The non-governmental organizations are not profit-making institutions (they are not primarily focused on commerce). This, however, does not mean that these organizations may not run an enterprise. Even though associations and foundations may have very similar aims, there are important difference between these institutions, such as the way they are formed, their organization and the economic matters. Associations and foundations may use various ways to receive funds for their charter enterprise. One of these ways is through an enterprise, which should provide an income (profit) covering the costs of a charter enterprise. The aim of this paper is to clarify the matter of an enterprise on the example of a foundation. The later is based on an Act pertaining to foundations and foundation charter. The foundation charter should determine the name of the foundation, its headquarters, property, aims and principles, the forms and scope of activity, the make-up, the way of appointment and organization of the board, as well as the responsibilities and powers of the authority and its members. The charter may also comprise of other resolutions, such as the running of an enterprise by the foundation, the admissibility of merging with another foundation and its terms, the changes in its aims or charter.
Keywords: fundacja; organizacja pozarządowa; działalność gospodarcza